Performance of the rapid plasma reagin and the rapid syphilis screening tests in the diagnosis of syphilis in field conditions in rural Africa. Issue 4 (1st August 2002) - West, B; Walraven, G; Morison, L; Brouwers, J; Bailey, R
Abstract : Objectives: To assess the rapid plasma reagin (RPR) test performance in the field and to evaluate a new rapid syphilis test (RST) as a primary screen for syphilis. Methods: 1325 women of reproductive age from rural communities in the Gambia were tested for syphilis seropositivity using a RPR 18 mm circle card and a RST strip. Within 1 week a repeat RPR and a TPHA test were carried out using standard techniques in the laboratory. Results: Comparing field tests to a diagnosis of "active" syphilis defined as laboratory RPR and TPHA positive, the RPR test was 77.5% sensitive and 94.1% specific; the RST was 75.0% sensitive and 95.2% specific. The RST was easier to use and interpret than the RPR test especially where field conditions were difficult. In this setting with a low prevalence of syphilis in the community (3%), the chance of someone with a positive test being confirmed as having serologically active syphilis was less than 50% for both tests. Conclusions: The appropriateness of syphilis screening using RPR testing in antenatal clinics and health centres should be questioned if there is a low prevalence in the population, conditions for testing are poor, and resources limited. There is still an urgent need for an appropriate rapid syphilis test for field use.